Anticholinesterase and Pharmacokinetic Profile of Phenserine in Healthy Elderly Human Subjects - Greig, Nigel H.; Ruckle, Jon; Comer, Patrick; Brownell, Lidia; Holloway, Harold W.; Flanagan Jr., Douglas R.; Canfield, Craig J.; Burford, Robert G. (Current Alzheimer Research, 2005)
Objective: To evaluate the safety, maximum tolerated dose (MTD), pharmacokinetics (PK), and pharmacodynamics (PD) of the acetyl-selective anticholinesterase, phenserine tartrate, in healthy elderly subjects. Methods: 32 healthy elderly volunteers received single oral doses of phenserine tartrate (5-20 mg). Physical and vital signs were monitored over the ensuing 24 hours. Analyses were performed on plasma samples to determine PK, and PD were assessed using an erythrocyte acetylcholinesterase (AChE) inhibition assay. Results: No serious adverse events (AEs) occurred; the most common were headache and vomiting. The MTD of phenserine tartrate was 10 mg. The Cmax and AUC(0-24) of phenserine increased with dose, but neither were doseproportional. Subjects receiving 10 mg of phenserine tartrate had a Cmax of 1.95 ng/mL at 1.5 hours, and the mean peak inhibition (Imax) of AChE was 26% (range: 18-34%) at 1.75 hours (tImax) following dosing. The half-life of AChE inhibition (tI1/2) was 11 hours. Evaluation of PK/PD relationships suggested a linear correlation between plasma phenserine concentration and AChE inhibition in the blood. Conclusions: Phenserine tartrate was safe and well tolerated when administered as a single oral dose of either 5 mg or 10 mg. An increase in the severity and frequency of AEs occurred at the 20 mg dose level.
Keywords: pharmacodynamics